Titus Maccius Plautus Trinummus (1-601, 820-42a): critical edition and commentary with an introduction - Giordani, D (2019)
My dissertation provides a new critical edition and commentary of Plautus’ Trinummus (ll. 1-601, 820-42a), along with an introductory section. The introduction is divided in six chapters: